(untitled) (Journal of EAHIL, 2021)
Early in the pandemic, as scientific reports and preliminary research on both clinical and public health aspects of COVID-19 were rapidly generated, we recognised the need for a dynamic, interactive tool that could capture and collate emerging evidence sources to inform research and decision-making efforts. In particular, we observed that numerous similar research efforts across the globe were happening in parallel - prompting an urgent need to connect research teams with each other and maximize research efficiency. Our colleagues in China provided daily translations of emerging evidence to aid networking between research groups working across the world. Here we describe how the meta-evidence project met daily and ongoing challenges and what was learned as a result. We describe the benefit of finding ways to instead work with better resourced teams and promote collective and open efforts to synthesise the evidence, which in the end, outweighed the considerable costs.